What an owl knows ebook The new science of the world's most enigmatic birds. - Ackerman, Jennifer (2023)
An instant New York Times bestseller! A New York Times Notable Book of 2023 Named a Best Book of 2023 by Publishers Weekly From the author of The Genius of Birds and The Bird Way , a brilliant scientific investigation into owls—the most elusive of birds—and why they exert such a hold on human imagination With their forward gaze and quiet flight, owls are often a symbol of wisdom, knowledge, and foresight. But what does an owl really know? And what do we really know about owls? Some two hundred sixty species of owls exist today, and they reside on every continent except Antarctica, but they are far more difficult to find and study than other birds because they are cryptic, camouflaged, and mostly active at night. Though human fascination with owls goes back centuries, scientists have only recently begun to understand the complex nature of these extraordinary birds.   In What an Owl Knows , Jennifer Ackerman joins scientists in the field and explores how researchers are using modern technology and tools to learn how owls communicate, hunt, court, mate, raise their young, and move about from season to season. Ackerman brings this research alive with her own personal field observations; the result is an awe-inspiring exploration of owls across the globe and through human history, and a spellbinding account of the world’s most enigmatic group of birds.